The pharmacokinetics of nitrofurantoin in healthy female volunteers: a randomized crossover study. (11th March 2019) - Huttner, Angela; Wijma, Rixt A; Stewardson, Andrew J; Olearo, Flaminia; Von Dach, Elodie; Harbarth, Stephan; Brüggemann, Roger J M; Mouton, Johan W; Muller, Anouk E
Abstract: Background: Use of nitrofurantoin has increased significantly since its recent repositioning as a first-line agent for uncomplicated cystitis by multiple guidelines. However, current dosing regimens were developed in an era before robust pharmacokinetic testing and may not be optimal. Furthermore, formulations have been modified over the years. Objectives: To reassess the plasma and urinary pharmacokinetic profile of macrocrystalline nitrofurantoin in two commonly used dosing regimens. Methods: In this open-label, randomized crossover pharmacokinetic trial, 12 healthy adult female volunteers were randomized to receive oral nitrofurantoin 100 mg q8h on days 1 and 2 and, after a washout period, 50 mg q6h on days 30 and 31, or the same dosing schemes in reversed order. Urine and blood were collected at steady state and analysed by UPLC. Pharmacokinetic analysis was performed by WinNonlin. Results: Plasma peak concentrations were low (mean 0.33 mg/L, SD 0.08, and 0.69 mg/L, SD 0.35, after 50 and 100 mg, respectively) and dose dependent. The AUC0–24 was higher (6.49 versus 4.43 mg·h/L, P  = 0.021) for the 100 mg q8h dosing regimen, but the dose-normalized AUC was similar for the two regimens. In contrast, urinary concentrations were dose independent: increasing the nitrofurantoin dose delayed the time to peak urinary concentration, while steady-state AUC0–24 values remained unchanged (943.49 and 855.95 mg·h/L at 50 mg q6h and 100 mg q8h, respectively). Conclusions: Plasma concentrations were relatively low and dose dependent. The dose-independent urinary concentrations suggest that excretion of nitrofurantoin into the urine is saturable. Pharmacodynamic studies are urgently required to determine the impact of these findings.